The creation of regional blocs in the world economy - Frans Buelens (Intereconomics, 1992)
International economic relations today show a rather pessimistic picture, with high non-tariff barriers, international trade frictions and a serious crisis in the GATT. The following article analyses present tendencies towards the creation of regional economic blocs and the threats to the world economy which these involve.
Keywords: 330; International Trade